Prehistoric Human Forensic DNA Analysis From Lore Highlands, Central Sulawesi With Present Day Human DNA - Najlaa Illiyyien Hadid; Indra Lesmana; Niken Satuti Nur Handayani; Dwi Yani Yuniawati Umar (KALPATARU, 2022)
Mitochondrial DNA or mtDNA(s) are inherited maternally, in other words they can only be inherited through females in a family, which makes them frequently used in forensic studies. In this research, the Hypervariable-I part (HV-1) in the D-Loop region of the ancient forensic samples acquired from Lore Highlands will be compared with present day human DNA from the same region. The steps conducted in this research includes DNA extraction, mtDNA amplification with specific primers, sequencing, and phylogenetic analysis. The analysis were done between 4 ancient forensic samples; A, B, G, and J, and 33 comparison sequences from GenBank, including ancient forensic sample acquired from Tadulako site, Lore Highlands, from previous research. The result of genetic distance analysis showed that the distance between 37 samples were very close; with difference ranging from 0,02% - 0,13%. The analysis also gives a clue about Austronesian relation with Australomelanesian. The result from phylogenetic tree reconstructions (maximum-likelihood and neighbor-joining) showed little differences. However, there is a small significant difference detected from the neighbour-joining tree construction result and will be discussed further in this paper.